Mutational analysis of the PA and PB2 subunits of the influenza RNA polymerase complex leads to new insights into function - Fodor, E; Fechter, P; Crow, M; Deng, T; Mingay, L; Sharps, J; Brownlee, G (2004)
The RNA-dependent RNA polymerase complex of influenza A virus consists of three subunits, PB1, PB2 and PA. To investigate the function of the PA subunit, we mutated evolutionarily conserved amino acids to alanines in the C-terminal third of PA of influenza A/WSN/33 that shows the highest degree of conservation between PA proteins of influenza A, B and C viruses. A H510A mutation inhibited the endonuclease cleavage of capped RNAs, K539A downregulated replication, while R638A resulted in severe attenuation of viral growth in cell culture by promoting the synthesis of defective interfering (DI) RNAs. Our results show that PA is required for both transcription and replication and that, in addition to its role in endonuclease cleavage, it might also act as an elongation factor during viral RNA synthesis. To investigate the function of PB2 in cap binding, we mutated all evolutionarily conserved aromatic amino acids of PB2 of influenza A/WSN/33. Our results suggest that F363 and F404 bind the cap structure of mRNA in an aromatic sandwich as in the evolutionarily unrelated VP39, eIF4E and CBP20. (C) 2003 Elsevier B.V. All rights reserved.